2023
DOI: 10.1093/humrep/dead047
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between mothers and children in families formed by shared biological motherhood

Abstract: STUDY QUESTION Does shared biological motherhood, in which a woman gives birth to the genetic child of her female partner, result in more positive mother–child relationships than donor insemination, in which only one mother is biologically related to the child? SUMMARY ANSWER Mothers in both family types showed high levels of bonding with their children and viewed their relationship with their child positively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…Although research on parity has demonstrated that nurturing experiences might be linked to maternal responses also to unfamiliar infant cues ( Maupin et al., 2019 ; Rutherford et al., 2019 ), it might be that, whilst unfamiliar infant faces engage the attention of mothers no matter their level of involvement, a higher level of commitment in childcare would be related to an increase of maternal RTs to own infant faces. Overall, our results empathize the importance of same-sex mother's involvement in childcare, which might be related to cognitive mechanisms underlying human caregiving (i.e., attentional bias to infant faces) and ultimately linked to a positive mother–child relationship ( Golombok et al., 2023 ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although research on parity has demonstrated that nurturing experiences might be linked to maternal responses also to unfamiliar infant cues ( Maupin et al., 2019 ; Rutherford et al., 2019 ), it might be that, whilst unfamiliar infant faces engage the attention of mothers no matter their level of involvement, a higher level of commitment in childcare would be related to an increase of maternal RTs to own infant faces. Overall, our results empathize the importance of same-sex mother's involvement in childcare, which might be related to cognitive mechanisms underlying human caregiving (i.e., attentional bias to infant faces) and ultimately linked to a positive mother–child relationship ( Golombok et al., 2023 ).…”
Section: Discussionsupporting
confidence: 60%
“…However, future research could focus on this topic embracing the complexity of different types of mother–child relationships, paying much attention to the new reproductive options (i.e., ROPA, Reception of Oocytes from the Partner), to take those factors into account also in the statistical models. Importantly, investigating the role of biological relatedness with the child might strengthen the idea that biological processes might explain only partially maternal responsiveness to infant cues, and that maternal involvement is important for mother–infant bondings besides the experience of pregnancy and birth ( Golombok et al., 2023 ). Moreover, since infants’ facial expressions might convey important information for understanding infants’ physical and mental needs, further research should explore more in depth the role of the emotional valence of facial expressions in maternal responses to infant faces.…”
Section: Limits and Future Directionsmentioning
confidence: 99%
“…As reciprocal IVF offers mothers the chance to 'share' biological motherhood, this biological inequality is reduced, and so questions of 'mine more than yours' may become obsolete. Indeed, quantitative research suggests that there are no differences in parent-child relationship quality between gestational and genetic mothers in reciprocal IVF families (Golombok et al, 2023). However, understandings of kinship are complex: societal discourse valorises genetic relationships, legal definitions of motherhood are centred on pregnancy and everyday understandings of kinship may encompass both.…”
Section: Two-mother Familiesmentioning
confidence: 99%
“…A positive and secure attachment fosters healthy connections and interactions for the child, potentially impacting their future parenting experiences [ 14 ]. Researchers pointed out that the mother-children relationship begins during pregnancy and continues throughout the child’s life [ 15 ]. For instance, it is evident that a better mother-children relationship during pregnancy is associated with a better maternal-infant relationship after birth [ 16 ].…”
Section: Introductionmentioning
confidence: 99%